Prior justification in urgency injury - A form of consecration of personal rights in family law, an analysis before the jurisprudence of the Court of Justice of the State of Paraná (Revista Direito em Debate, 2023)
It seeks to analyze the use of the prior justification provided for in §2 of art. 300 of the CPCP/2015, as a way to resolve doubts that can be resolved with the presentation of additional evidence that can assist in the best analysis for the possible acceptance of the urgency claim, with a special focus on personality rights along with family law. The study will take place through a bibliographic review that will show the use of the procedural file studied as a way to clarify small doubts that the Magistrate may have regarding the probability of the right and the danger of damage or the risk to the useful result of the process, requirements of the caput of art. 300 of the CPC. Also for a jurisprudential review that will highlight the criteria for granting the intended emergency injunctions, as well as demonstrating that the prior justification hearing is an important tool for the realization of alternative means of conflict resolution enshrined in art. 3, §3 of the CPC, thus promoting the achievement of the full solution of the merits, including the satisfactory activity within a reasonable period, as provided for in art. 4 of the CPC, since in the justification hearing, the parties are able to reach a consensual resolution of the demand.
Keywords: Emergency provisional relief; Prior justification; Personality rights; Civil procedural law; Alternative means of conflict resolution